ISSUES AND ESSENCE OF INTERACTION BETWEEN THE SUBJECTS ADMINISTRATIVE AND LEGAL PROVISION OF INFORMATION SECURITY IN THE CUSTOMS SPHERE - Салаєв, Тургут Гаджи огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The aim of the article: the article studies the concepts and reveals the essence of the interaction of the subjects of information security in the customs sphere of Ukraine. Research design: formal legal and system-structural methods were used in the article. Results: based on the analysis of historical and modern scientific approaches, doctrinal approaches to the interpretation of the category «interaction» and its features were summarized. On this basis, we propose our own understanding of the concept of «interaction between entities in order to ensure information security in the customs field» and its essential features. Interaction as a co-ordinated activity of the subjects of administrative and legal support of information security in the customs sphere is structured according to the levels of its subjects, firstly by identifying the central subject of such interaction by the customs authorities. The corresponding provisions of the regulatory framework in the corresponding field are summarized and characterized. A special attention is paid to the particular information of the departmental acts of the customs authorities, which contain statistics on interactions with other information security entities. In the article the author focuses on the fact that today the interaction between the subjects on information security in the customs field is not properly formed and it is still on the stage of formation. The disadvantages and problematic issues of interaction between the subjects on providing information security in the customs field are highlighted. Among them we can name such as: the inconsistency, non-coordination of activities and other forms of interaction between the subjects of information security in the customs field, legal uncertainty and non-systematic regulation of the interaction of subjects on information security in the customs field, improper initiative of the customs authorities as the main and coordinating entity of provision of information security in the customs field, unsettled issue of public control in the field of information security in the customs sphere. The author makes suggestions about the necessity to develop and deepen interaction between the subjects of administrative and legal support of information security in the customs field. Some directions for overcoming these problems are suggested.